Supporting Parents in their Parental Role - Approaches Practiced by Preschool Teachers in Preschool - Vuorinen, Tuula (International Journal about Parents in Education, 2023)
The purpose of this paper is to analyze and discuss preschool teachers’ supportive approaches when supporting parents within their profession. Questions addressed are; what kind of supporting approaches do preschool teachers practice to strengthen parents in their parental role? Which theoretical frameworks do preschool teachers use when supporting parents in their parental role? Results, based on interviews with 30 preschool teachers in Sweden, show that the participating preschool teachers share an ambition to support and strengthen parents in their parental role. To do so preschool teachers practice and use different approaches - the teambuilding-, the reflective-, the expert-, the delimited- and the personal approach. The approaches used in practice do not, however, always serve their purpose, but on the contrary, preschool teachers may weaken parents’ self-efficacy. The different approaches also show that preschool teachers not always “preach as they teach”, using different theoretical perspectives in their collaboration with parents as they do in their own practice at preschool. The results from this study are important to reach a deeper understanding for underlying factors, as e. g. different views of children, in preschool and home collaboration.